Evaluation of the anti-cancer effects of novel pyrrolo-1, 5-benzoxazepines in neuroblastoma - Lennon, Jennifer (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2015)
Neuroblastoma, a malignancy of neuroectodermal origin, accounts for 15% of childhood cancer deaths. Despite both advances in understanding the biology of the cancer and aggressive treatment strategies, it continues to be one of the most difficult paediatric cancers to successfully treat. More than 60% of patients present at diagnosis with adverse features, and less than 40% of these achieve disease free long term survival. A major obstacle in the effective treatment of neuroblastoma is the development of multidrug resistance (MDR) to a broad range of cytotoxic drugs. This MDR phenotype often includes amplification of the proto oncogene MYCN, mutation/deletion of p53, deletion of loci at 1p or 11q and over expression of MDR proteins leading to altered drug transport and an increase in drug efflux. There is thus a compelling demand for new/ treatment strategies for this cancer that can bypass such resistance mechanisms.
Keywords: Biochemistry & Immunology, Ph.D.; Ph.D. Trinity College Dublin